FORMULASI SPRAY GEL EKSTRAK ETANOL BIJI KEDELAI (Glycine max) SEBAGAI SEDIAAN KOSMETIK TABIR SURYA - Ayu Shabrina; Faza Putri_Maulina Hanik; M_Rifki Pratama_Kharisma Akbar; Elya Zulfa (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2020)
ABSTRACT Skin damage caused by free radicals disturbs the health of human skin that needs protection. Soybean extract showed that its SPF value was 6,93 on concentration of 0,5%. The purpose of this study was to determine the effect of variation concentrations of Soybean Seed Ethanol Extract (SSEE) on spray gel characteristic and sunscreen activity in vitro. Soybean seeds were extracted by maceration method using 96% ethanol solvent. Extracts obtained were made into spray gel preparation with variations of SSEE concentration were 2% (F1), 4% (F2), 6% (F3). SSEE spray gel was tested for organoleptic, homogeneity, pH, viscosity, spraying pattern and sunscreen activity test. Data from organoleptic, homogeneity, viscosity, pH and spray patterns and sunscreen activity were analyzed descriptively while viscosity was analyzed using linear regression. The spray gels were homogenous with thick texture, and brownish yellow color also distinctive aroma of soybean seeds. Based on the test results, variations concentrations of SSEE did not affect the spray gel characteristics except the viscosity that decreased. Sunscreen activity test showed that SPF values were 13.82 (F1), 13.96 (F2) and 14.54 (F3) included maximal protection. Keywords: soybeans, sunscreen, spray gel, in vitro